2019
DOI: 10.4103/bc.bc_54_19
|View full text |Cite
|
Sign up to set email alerts
|

Review of selective brain hypothermia in acute ischemic stroke therapy using an intracarotid, closed-loop cooling catheter

Abstract: In acute ischemic stroke patients, selective brain hypothermia is a promising concept aiming at a fast decrease of brain temperature and thus neuroprotection in the acute phase of ischemia. At the same time, the emergence of mechanical thrombectomy (MT) as an effective treatment in large-vessel occlusion opens the door for a combination of neuroprotective approaches in the frame of a neurovascular, catheter-based intervention. In this regard, intracarotid cooling is a very effective energetic approach, using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…In recent years, methods have been well established to achieve rapid cooling in patients using whole-body techniques such as endovascular or skin cooling ( 15 ). Direct brain cooling strategies such as intranasal ( 36 ) and intracarotid cooling ( 37 ) are less well established but are under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, methods have been well established to achieve rapid cooling in patients using whole-body techniques such as endovascular or skin cooling ( 15 ). Direct brain cooling strategies such as intranasal ( 36 ) and intracarotid cooling ( 37 ) are less well established but are under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The distal end of the CLCC consists of four balloons with a diameter of 4 mm and a length of 20 mm each, spaced from each other by 4 mm, resulting in a total length of 92 mm. 17 , 19 , 20 Two catheter lumina with an inner diameter of around 1 mm each enable a continuous closed-loop flow of cold saline into and out of the balloons, respectively. The catheter also features a central lumen compatible with a 6 F catheter for MT procedures during cooling, resulting in a 3.4 mm outer diameter (corresponding to an 11 F catheter or to an 8 F sheath).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, rapid and early endovascular selective brain cooling combined with MT may be an appealing alternative TH approach for neuroprotection in LVO stroke. 4 , 6 , 17 , 18 A recent study including 113 LVO patients demonstrated safety of a combined therapy applying a standard MT plus a short (15 min) intra-arterial (‘selective’) cold saline infusion versus MT alone. 6 Moreover, a trend towards improved functional outcome was observed in the selective TH group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant neuroprotection was obtained when hypothermia was started within therapeutic time window of 4 h after reperfusion in rat model (6). Furthermore, in patients with middle cerebral artery infarction, therapeutic hypothermia treatment can significantly reduce intracranial pressure, alleviate cerebral edema, and improve neurological dysfunction (7,8). Furthermore, a number of studies have investigated the potential for combination of mild hypothermia with drug therapy, which was proved to be more effective in protecting neurons than hypothermia alone in an experimental model of cerebral ischemia (6).…”
Section: Introductionmentioning
confidence: 99%